REVITALIZATION OF KAWALI FOLKLORE IN THE FORM OF 2D ANIMATED DIGITAL STORYTELLING AS A MEDIUM FOR ORAL LITERATURE LEARNING AT THE COMMUNITY READING PARK OF CIAMIS REGENCY - Andri Noviadi; Sri Mulyani; H.R. Herdiana; Meisa Syaidah Hufa; Chindi Febrianti (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research addresses the erosion of Kawali folklore by transforming it into 2D animated digital storytelling, aiming to preserve local culture and provide engaging oral literature learning media, particularly for Community Reading Gardens (TBM) in Ciamis Regency. The research adopted the Research and Development (R&D) method, encompassing phases from data collection and script adaptation to 2D animation production using Toon Boom Harmony and Adobe After Effects. The primary finding was the documentation and selection of "The Legend of the Origin of Kawali" (Legenda Asal-Usul Kawali) due to its significant values regarding sacrifice and toponymy. The output is a narrative audiovisual script and an animated short film currently 80% complete, featuring simplified plots and culturally authentic character designs (Ki Bondan and Ajar Sukaresi). The study concludes that 2D animated digital storytelling is a highly effective, innovative, and relevant solution for integrating local wisdom into literacy programs, fostering cultural preservation, and enhancing reading interest among the digital generation at TBM Gada Membaca Kawali.